2004
DOI: 10.1037/0022-3514.86.6.796
|View full text |Cite
|
Sign up to set email alerts
|

The Social Cognition of Immigrants' Acculturation: Effects of the Need for Closure and the Reference Group at Entry.

Abstract: Three studies found support for the notion that immigrants' acculturation to the host culture is interactively determined by their need for cognitive closure (A. W. Kruglanski & D. M. Webster, 1996) and the reference group they forge on their arrival. If such reference group is fashioned by close social relations with coethnics, the higher the immigrants' need for closure, the weaker their tendency to assimilate to the new culture and the stronger their tendency to adhere to the culture of origin. By contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 59 publications
5
87
1
4
Order By: Relevance
“…Por último, si bien existen un gran número de teorías e investigaciones empíricas que han abordado los factores contribuyentes a la exclusión social y los procesos de aculturación inmigrante, en el estudio de tales dinámicas no ha sido habitual analizar conjuntamente el sexismo, las diferencias culturales asociadas a la religión y la necesidad de cierre cognitivo (Berry, 2001;Hitti, Mulvey y Pillen, 2011;Kosic, Kruglanski, Pierro y Mannetti, 2004;Navas, Rojas y García, 2011). En base a lo expuesto, en la presente investigación se pretende estudiar dicho constructo motivacional y su relación con el sexismo y la religiosidad, así como las interrelaciones entre éstos; factores psicosociales, todos ellos, muy dependientes de la cultura y de permanente actualidad.…”
Section: Introductionunclassified
“…Por último, si bien existen un gran número de teorías e investigaciones empíricas que han abordado los factores contribuyentes a la exclusión social y los procesos de aculturación inmigrante, en el estudio de tales dinámicas no ha sido habitual analizar conjuntamente el sexismo, las diferencias culturales asociadas a la religión y la necesidad de cierre cognitivo (Berry, 2001;Hitti, Mulvey y Pillen, 2011;Kosic, Kruglanski, Pierro y Mannetti, 2004;Navas, Rojas y García, 2011). En base a lo expuesto, en la presente investigación se pretende estudiar dicho constructo motivacional y su relación con el sexismo y la religiosidad, así como las interrelaciones entre éstos; factores psicosociales, todos ellos, muy dependientes de la cultura y de permanente actualidad.…”
Section: Introductionunclassified
“…Kashima and Loh (2006) argued that social ties seen in the various networks play an important role in helping newcomers" psychological adjustment, or emotional wellbeing and satisfaction during the cultural transition. For example, they found that strong ties with co-nationals offer psychological support and help the newcomers with a cultural identity related to their own cultural heritage Kosic et al (2004) reported that Asian international students face the task of learning about interpersonal norms. Their study indicated that international students with more local and international ties seem to more easily adapt to the new culture, whereas those who have more co-national ties, but less international ties seem to have difficulties with cultural adjustment.…”
Section: Cultural Shockmentioning
confidence: 99%
“…The above results are derived from a wide variety of studies, their topics extend over subjects such as abstract problems (Jaśko et al, 2015), consumer decisions (Houghton & Grewal, 2000), and actual behavior in a social context (Kosic et al, 2004). These effects are present both in studies that operationalize the need for closure as a dispositional variable (e.g., Bar-Tal et al, 1997, 2010 and in those that operationalize it as a situational variable (e.g., Mayseless & Kruglanski, 1987;Kossowska & Jaśko, 2013).…”
Section: The Dual Consequences Of the Need For Closure And The Need Tmentioning
confidence: 99%
“…An interesting example of the two fold consequences of a high need for closure in social situations has been provided in the study conducted by Kosic, Kruglanski, Pierro, and Mannetti (2004) on immigrants' tendency to assimilate, depending on their level of their need for closure and on the groups in which they functioned. According to their results, high need for closure resulted in a lower tendency to assimilate if, following immigration, the participants functioned in a group composed of representatives of their own ethnic group.…”
Section: The Dual Consequences Of the Need For Closure And The Need Tmentioning
confidence: 99%